Two Open-Access Experiments in HSS: Journal and Monograph Publishing - Neuman, Yrsa (Septentrio Conference Series, 2014)
See video of the presentation. Within the Agora project (2011-13), two Open Access experiments in HSS Open Access publication, within philosophy specifically, have been carried out. One with journal publishing, one with monograph publishing. Our preliminary monograph experiment results show that certain hybrid Open Access business models are very promising for publishers and scholars alike. For the 27 monographs from Ontos Verlag which were made OA, access to the publications rose remarkably and our results show that OA does not reduce revenue - instead it either increases revenue or is revenue neutral. Our journal experiment shows that Open Review and Open Access can well be combined with a printed journal, and that delays do not prohibit sales to libraries. I will tell you how, and why, in my presentation. Apart from the results of our study, I will discuss some of the difficulties which hybrid OA publications may run into.